Benthic visual adaptation by fine-tuning light sensitivity in Japanese flounder (Paralichthys olivaceus) - Zhang, Zhengrui; Liu, Yuezhong; Zhang, Wei; Du, Xinxin; Liu, Jinxiang (Frontiers in Marine Science, 2022)
The habitat occupied by flatfish fry differs considerably in light regime from that of the adult. The diversity of opsins and their expression patterns appear greatest for flatfishes to experience variable light environments. Yet, opsin repertoires and expression patterns in this group of fishes are poorly described. To understand how the visual system has adapted to such changes, we unveil that Japanese flounder (Paralichthys olivaceus) has a visual system adapted to a benthic environment by fine-tuning paralogous opsins (SWS2A and RH2) for wavelength shift and regulated expression. P. olivaceus express five basic opsin genes (M/LWS, SWS1, SWS2, RH1 and RH2) and gene-specific duplications were observed in RH2 and SWS2 paralogues. The expression of the three short-wavelength sensitive genes, SWS2Aα, SWS2Aβ, and SWS2B, is significantly elevated at the benthic stages, especially in SWS2Aβ a striking expression change is observed. The four middle-wavelength sensitive genes exhibit divergent expressions, the expression of RH2A-1 and RH2A-2 increased, while that of RH2B-1 and RH2B-2 decreased significantly from pelagic to benthic stage, especially RH2A-2. At present, changes at a total of 26 sites are known to have modified the λmax of various visual pigments during vertebrate evolution. Thus, these tuning site variations in our P. olivaceus are suspected to cause a green-shift in the λmax of SWS2Aα pigments and blue-shift in that of in RH2A-2. Together, our results suggest that RH2 and SWS2 opsin repertoires serve to optimize visual function under variable light environments by gene family duplications, differential expressions, and maximum absorption wavelength (λmax) variations.